1993
DOI: 10.1346/ccmn.1993.0410203
|View full text |Cite
|
Sign up to set email alerts
|

Illite/Smectite Geothermometry of the Proterozoic Oronto Group, Midcontinent Rift System

Abstract: Abstract--Characterization of the Nonesuch Formation, middle unit of the Proterozoic Oronto Group, as a potential hydrocarbon source for the Lake Superior basin portion of the Midcontinent Rift system requires an understanding of the thermal maturity of the region and its relationship to the thermal history. Illite/smectite (I/S) expandability data were collected from the Nonesuch Formation and the overlying Freda Sandstone and compared with organic thermal maturity data; both data sets coupled with a thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 27 publications
4
26
0
Order By: Relevance
“…Such maximum paleotemperature estimation based on %S seems to apply also to Precambrian rocks. For instance, Price and McDowell (1993) have shown that, without experiencing sufficiently high temperatures sometime during their geological history, clays as old as Precambrian stay highly expandable.…”
Section: Geological Implicationsmentioning
confidence: 99%
“…Such maximum paleotemperature estimation based on %S seems to apply also to Precambrian rocks. For instance, Price and McDowell (1993) have shown that, without experiencing sufficiently high temperatures sometime during their geological history, clays as old as Precambrian stay highly expandable.…”
Section: Geological Implicationsmentioning
confidence: 99%
“…1993, Pollastro 1993. Price and McDowell (1993) advanced a T-t model for clay transformations observed in 1.1 Ga old pelites of the Nonesuch Formation, Michigan. Pollastro (1993) inferred that different T-t relations apply to sediments of Miocene through Mississippian age and those <3 Ma in age.…”
Section: What Can Clays Contribute To Geothermometry?mentioning
confidence: 99%
“…With increasing depth of burial in sedimentary basins there is a progressive conversion of smectite into illite and the extent of reaction is frequently used as an indicator of diagenetic grade (Hoffman and Hower 1979, H6roux et al 1979, Pollastro 1990, Price and McDowell 1993. However, besides the increase of temperature with depth, many other factors may influence the progress of this reaction complicating attempts to use it as a geothermometer.…”
Section: Introductionmentioning
confidence: 99%